The Association of Malnutrition, illness duration, and pre-morbid weight status with anxiety and depression symptoms in adolescents and young adults with restrictive eating disorders: a cross-sectional study - Jessica A. Lin; Grace Jhe; Julia A. Vitagliano; Carly E. Milliren; Rebecca Spigel; Elizabeth R. Woods; Sara F. Forman; Tracy K. Richmond (Journal of Eating Disorders, 2021)
Plain english summary People with eating disorders (EDs) often also struggle with anxiety and depression. Unfortunately, this can mean their disease is more severe, harder to treat, and more dangerous and potentially fatal. ED treatment often primarily focuses on nutrition and weight gain, and sometimes loses focus on the person’s mood and anxiety. Additionally, patients can present at any weight, but not enough is known about how baseline weight before weight loss might affect mood. In this study, we focus on adolescents/young adults with restrictive EDs to understand what places them at risk for depression and anxiety. We find that the majority of our participants have clinically significant anxiety and depression. However, degree of malnutrition was not related to level of anxiety and depression. Struggling with an ED for longer time was associated with increased depression and possibly anxiety as well. We also find that those who had relatively high baseline weights prior to weight loss had lower depression and anxiety scores than those who had lower baseline weights. Early identification and treatment of individuals with EDs is important, and there are likely other factors beyond malnutrition that we need to understand in order to identify those at risk for depression and anxiety.